Erratum and Addendum: "Numerical and Experimental Investigation of Performance and Flooding Phenomena of a PEM Fuel Cell with and without Micro-Porous Layers" - Duong, Vu; Ha Hiep, Nguyen (Engineering, Technology & Applied Science Research, 2024)
The authors would like to declare that Figures 1-5 in [1] have previously been published (in part or in whole) in [2], which is referenced in [1] under reference number 16. The figures are reprinted in [1] with the permission of the Publisher and copyright owner of [2].